Sodium ion positive electrode material, preparation method thereof and sodium ion battery
By reacting chromium trioxide and sodium hydroxide at 280-330°C, a high-performance sodium ion positive electrode material was prepared, which solved the problem of poor circulation performance of transition metal layered oxide NaxMO2 in the prior art, and achieved high discharge specific capacity and good circulation performance of sodium ion batteries.
Patent Information
- Application Number
- CN202510133045.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-25
AI Technical Summary
The existing transition metal layered oxide NaxMO2 is poor in cycling performance when used as a positive electrode material, and cannot effectively improve the capacity and circulation performance of sodium ion batteries.
By mixing chromium trioxide and sodium hydroxide, drying, and reacting at 280-330°C, a sodium ion positive electrode material with high theoretical energy density and high operating voltage was prepared. This method generates layered oxides through the pyrolysis of chromium trioxide and direct reaction with sodium hydroxide, which improves the cyclic performance and reversible capacity of the material.
The discharge specific capacity and cycling performance of sodium ion batteries have been significantly improved, so that the sodium ion positive electrode material can be recharged and discharged repeatedly, and the cycling performance is better, and the performance is much higher than that of the existing transition metal layered oxide NaxMO2.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a sodium ion positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have been widely researched and developed in recent years. This type of battery uses materials that can store sodium ions instead of metallic sodium. Sodium compounds are abundant, easy to mine, and of high quality. The current collector can also use aluminum sheets instead of copper sheets, making it very competitive in the market. The transfer, storage, and release of sodium ions between positive and negative electrode materials are reversible. In theory, if the positive electrode material can carry more sodium ions, more sodium ions will be embedded in the negative electrode material, and the electrochemical performance of the resulting battery will be better. Compared with lithium-ion batteries, sodium-ion batteries have system advantages such as larger specific capacity, stronger diffusion ability, and lower desolvation energy.
[0003] In recent years, transition metal layered oxides Na x MO2 (M is a transition metal) is considered to be a suitable cathode material due to its feasible preparation method, high reversible capacity, high ionic conductivity and suitable working potential. x MO2 still has some disadvantages, such as limited reversible capacity and poor cycle performance. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the transition metal layered oxide Na x The defect of MO2 as a positive electrode material is poor cycle performance, so as to provide a sodium ion positive electrode material and a preparation method thereof, and a sodium ion battery.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a method for preparing a sodium ion positive electrode material, comprising the following steps:
[0007] Chromium trioxide and sodium hydroxide are mixed, dried, and reacted at 280-330° C. to obtain a sodium ion positive electrode material. Exemplarily, the reaction temperature is 280° C., 290° C., 300° C., 310° C., 320° C., 330° C., or within a range formed by any two of the above values.
[0008] Within the above temperature range, chromium trioxide can be fully pyrolyzed, and there will be no residual chromium trioxide with strong oxidizing properties to react with other substances to reduce the electrical properties of sodium ion positive electrode materials; nor will there be energy waste and a large number of by-products due to excessive temperature. After pyrolysis, chromium trioxide directly reacts with sodium hydroxide to obtain a layered oxide, which has the characteristics of high theoretical energy density and high working voltage, and can greatly increase the capacity of sodium ion batteries at low discharge rates, and improve cycle performance and reversible capacity.
[0009] In an optional embodiment, the molar ratio of the chromium element in the chromium trioxide to the sodium element in the sodium hydroxide is (4.8-5.2): 1. Exemplarily, the molar ratio of the chromium element in the chromium trioxide to the sodium element in the sodium hydroxide is 4.8:1, 4.9:1, 5.0:1, 5.1:1, 5.2:1 or within the range of any two of the above values.
[0010] In an optional embodiment, during the mixing, the chromium trioxide is mixed with the sodium hydroxide in a solid form.
[0011] In an optional embodiment, the drying temperature is 80-120°C; illustratively, the drying temperature is 80°C, 90°C, 100°C, 110°C, 120°C or in a range consisting of any two of the above values.
[0012] In an optional embodiment, the drying time is 8-12 hours. The purpose of drying is to remove the adsorbed water and crystal water in the chromium trioxide and sodium hydroxide, improve the purity of the raw materials, and avoid the adverse effects of moisture in the reaction, which affects the performance of the sodium ion positive electrode material;
[0013] In an optional embodiment, the reaction is carried out under an oxygen atmosphere;
[0014] In an optional embodiment, the oxygen volume content of the oxygen atmosphere is 90-100%. Exemplarily, the oxygen volume content of the oxygen atmosphere is 90%, 92%, 94%, 96%, 98%, 100% or within the range of any two of the above values.
[0015] The reaction is carried out in an oxygen volume content of 90-100%, so that the generation of impurities can be avoided, and the electrical properties of the sodium ion positive electrode material prepared by the present invention can be further improved.
[0016] In an optional embodiment, the heating rate of the reaction is 1-5°C / min; illustratively, the heating rate of the reaction is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or within a range formed by any two of the above values.
[0017] In an optional embodiment, the reaction time is 40-50 hours. Exemplarily, the reaction time is 40 hours, 42 hours, 44 hours, 46 hours, 48 hours, 50 hours, or within a range formed by any two of the above values.
[0018] In an optional embodiment, the mixing includes: first mixing at 1000-1200 r / min for 10-12 min, and then mixing at 2500-3000 r / min for 15-20 min;
[0019] The present invention also provides a sodium ion positive electrode material prepared by the above preparation method.
[0020] The sodium ion positive electrode material prepared by the present invention has good discharge specific capacity and cycle performance after being made into a battery. The sodium ion positive electrode material prepared by the special process and raw materials of the present invention can be repeatedly charged and discharged.
[0021] The present invention also provides a sodium ion battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises the sodium ion positive electrode material prepared by the above preparation method;
[0022] Preferably, the sodium ion battery further comprises a negative electrode plate, and the negative electrode active material of the negative electrode plate comprises graphite.
[0023] The technical solution of the present invention has the following advantages:
[0024] 1. The preparation method of the sodium ion positive electrode material provided by the present invention comprises the following steps: mixing chromium trioxide and sodium hydroxide, drying, and reacting at 280-330°C to obtain the sodium ion positive electrode material. The sodium ion positive electrode material prepared by the present invention has good capacity and cycle performance. Specifically, chromium trioxide has a higher theoretical energy density and operating voltage, can accommodate more sodium ions, and at the same time, the chromium element can be converted from hexavalent to trivalent to achieve multi-electron transfer, which effectively improves the capacity and cycle performance of the material. In addition, the sodium ion positive electrode material prepared by the present invention is significantly reduced in capacity compared to NaCrO2 or Cr8O 21, can be repeatedly charged and discharged, and has better cycle performance. The present invention directly mixes chromium trioxide and sodium hydroxide and then heats the temperature to 280-330°C for reaction. The process first pyrolyzes the chromium trioxide, and the pyrolysis product then reacts with sodium hydroxide, thereby avoiding contamination during the process of pyrolyzing the chromium trioxide and then mixing it with sodium hydroxide. This improves the purity of the prepared positive electrode material and can fully utilize the advantage of chromium in improving the material capacity and cycle performance, and reacts it with sodium to prepare a positive electrode material with high cycle performance and high reversible capacity. The performance of the positive electrode material prepared by the present invention using special processes and raw materials is much higher than that of the existing transition metal layered oxide Na x MO2.
[0025] 2. The preparation method of the sodium ion positive electrode material provided by the present invention is to add chromium trioxide in solid form for drying, remove the adsorbed water and crystal water in the chromium trioxide, and further make the chromium trioxide and sodium hydroxide fully react; first mix at 1000-1200r / min for 10-12min, and then mix at 2500-3000r / min for 15-20min; the chromium trioxide and sodium hydroxide can be better mixed, so that the subsequent reaction is more sufficient. Reacting in an oxygen volume content of 90-100% can avoid the generation of impurities, and further improve the performance of the prepared positive electrode material.
[0026] 3. The sodium ion battery provided by the present invention uses graphite as the negative electrode active material, which can buffer the volume change during the charge and discharge process, improve the integrity of the electrode structure, and effectively reduce costs. The present invention uses graphite as the negative electrode active material, which can better match the positive electrode plate and the negative electrode plate to give full play to their respective characteristics, and can further improve the battery's electrical performance. DETAILED DESCRIPTION
[0027] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0029] The invention provides a method for preparing a sodium ion positive electrode material, comprising the steps of mixing chromium trioxide and sodium hydroxide at 1000-1200 r / min for 10-12 min and then at 2500-3000 r / min for 15-20 min in a staged mixing manner, so as to facilitate subsequent full reaction of the two; drying at 80-120° C. for 8-12 h, wherein the purpose of drying is to remove adsorbed water and crystal water in the chromium trioxide and the sodium hydroxide, so as to avoid adverse effects of the water in subsequent reactions;
[0030] The mixed chromium trioxide and sodium hydroxide are heated to 280-330°C at 1-5°C / min in an oxygen atmosphere (90-100V%) and then maintained for 40-50h; the chromium trioxide can be fully pyrolyzed in the reaction at 280-330°C, and the pyrolysis product can directly react with sodium hydroxide to avoid air pollution and the generation of other impurities, which is conducive to obtaining high-performance sodium ion positive electrode materials.
[0031] The sodium ion positive electrode material prepared by the preparation method of the sodium ion positive electrode material provided by the present invention has significantly improved discharge specific capacity and cycle performance after being made into a battery.
[0032] Example 1
[0033] This embodiment provides a method for preparing a sodium ion positive electrode material, comprising the following steps:
[0034] Chromium trioxide and sodium hydroxide were mixed at 1000 r / min for 10 min, then at 2500 r / min for 15 min, dried in a vacuum oven at 120°C for 10 h, then moved into a tube furnace for reaction in an oxygen atmosphere (95V%), heated to 320°C at 5°C / min for 50 h, and a sodium ion positive electrode material was obtained. The molar ratio of chromium in chromium trioxide to sodium in sodium hydroxide was 5:1.
[0035] This embodiment also provides a method for preparing a sodium ion battery, comprising the following steps:
[0036] (1) The prepared sodium ion positive electrode material, polyvinylidene fluoride (PVDF), and carbon black were mixed in a mass ratio of 8:1:1, an appropriate amount of NMP was added, and the mixture was stirred with a magnetic stirrer for 10 hours to obtain a positive electrode slurry;
[0037] (2) The positive electrode slurry was evenly coated on the aluminum foil with a coating thickness of 120 μm, and dried in a vacuum drying oven at 80° C. for 10 h to obtain a positive electrode sheet;
[0038] (3) A graphite-coated copper foil was used as the negative electrode and a polypropylene was used as the separator, which were assembled in a glove box to obtain a sodium ion battery.
[0039] Example 2
[0040] This embodiment provides a method for preparing a sodium ion positive electrode material. Compared with Embodiment 1, the only difference is that the reaction temperature is 330° C. instead of 320° C. in Embodiment 1.
[0041] This embodiment also provides a sodium ion battery, which is prepared according to the method of Example 1.
[0042] Example 3
[0043] This embodiment provides a method for preparing a sodium ion positive electrode material. Compared with Embodiment 1, the only difference is that the reaction temperature is 300° C. instead of 320° C. in Embodiment 1.
[0044] This embodiment also provides a sodium ion battery, which is prepared according to the method of Example 1.
[0045] Example 4
[0046] This embodiment provides a method for preparing a sodium ion positive electrode material, comprising the following steps:
[0047] Chromium trioxide and sodium hydroxide were mixed at 2500r / min for 25min; dried in a vacuum drying oven at 120℃ for 10h; then moved into a tube furnace for reaction under an oxygen atmosphere (95V%), heated to 320℃ at 5℃ / min for 50h to obtain a sodium ion positive electrode material. The molar ratio of chromium in chromium trioxide to sodium in sodium hydroxide is 5:1.
[0048] This embodiment also provides a sodium ion battery, which is prepared according to the method of Example 1.
[0049] Comparative Example 1
[0050] This comparative example provides a method for preparing a sodium ion positive electrode material. Compared with Example 1, the only difference is that the reaction temperature is 250° C. instead of 320° C. in Example 1.
[0051] This comparative example also provides a sodium ion battery, which is prepared according to the method of Example 1.
[0052] Comparative Example 2
[0053] This comparative example provides a method for preparing a sodium ion positive electrode material. Compared with Example 1, the only difference is that the reaction temperature is 400° C. instead of 320° C. in Example 1.
[0054] This comparative example also provides a sodium ion battery, which is prepared according to the method of Example 1.
[0055] Comparative Example 3
[0056] This comparative example provides a method for preparing a sodium ion positive electrode material. Compared with Example 1, the only difference is that chromium hydroxide is used instead of chromium trioxide in Example 1.
[0057] This comparative example also provides a sodium ion battery, which is prepared according to the method of Example 1.
[0058] Test Case
[0059] The performance test of the sodium ion batteries prepared in each embodiment and comparative example was carried out using a blue electric test platform, as follows:
[0060] (1) 0.2C discharge capacity: at room temperature, 0.2C constant current charging to a voltage of 3 V, 3V constant voltage charging to a current of 20 mA, standing for 10 min, 0.2C constant current discharge to a cut-off voltage of 2 V, standing for 10 min, and the 0.2C discharge capacity is obtained. The results are shown in Table 1.
[0061] (2) Cyclic performance: At room temperature, charge at 0.2C constant current to 3V, charge at 3V constant voltage to 20mA, let stand for 10min, discharge at 0.2C constant current to cut-off voltage of 2V, let stand for 10min, and obtain 0.2C discharge specific capacity. Repeat the above steps 50 times. The results are shown in Table 1.
[0062] Table 1
[0063] 0.2C discharge capacity mAh / g Cycle performance (%) Example 1 210.5 81.2 Example 2 208.1 81.5 Example 3 205.9 77.6 Example 4 190.4 75.0 Comparative Example 1 120.1 50.3 Comparative Example 2 133.4 70.1 Comparative Example 3 100.1 49.1
[0064] The sodium ion positive electrode material prepared by the present invention has a high discharge capacity and good cycle performance after being made into a battery. It is explained that after chromium trioxide and sodium hydroxide are directly mixed and reacted at 280-330°C, the discharge capacity of the obtained positive electrode material after being made into a battery is ≥190.4mAh / g, and the cycle performance is ≥75.0%. It is further preferred to mix at 1000-1200r / min for 10-12min, and then mix at 2500-3000r / min for 15-20min; segmented mixing can better make chromium trioxide and sodium hydroxide react fully, further improving the discharge capacity and cycle performance of the sodium ion battery.
[0065] By comparing Examples 1-4 and Comparative Examples 1-3, it can be seen that when the reaction temperature is between 280-330°C, the obtained sodium ion positive electrode material has a high discharge capacity and good cycle performance after being made into a battery. Comparative Example 1 shows that when the reaction temperature is less than 280°C, a large amount of chromium trioxide will not be decomposed, which is easy to react directly with the electrolyte, causing the battery discharge capacity and cycle performance to deteriorate; Comparative Example 2 shows that when the reaction temperature is greater than 330°C, not only will there be energy waste, but other by-products will also appear due to excessively high temperature, causing the electrical performance of the obtained sodium ion battery to deteriorate. Comparative Example 3 shows that the positive electrode material prepared by replacing chromium trioxide with other chromium sources such as chromium hydroxide, the 0.2C discharge capacity and cycle performance of the battery after being made are significantly reduced, indicating that the present invention can only be used with chromium trioxide as a raw material, and the obtained positive electrode material has better performance.
[0066] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a sodium ion positive electrode material, characterized in that: The steps include: Chromium trioxide and sodium hydroxide are mixed, dried, and reacted at 280-330° C. to obtain a sodium ion positive electrode material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the chromium element in the chromium trioxide to the sodium element in the sodium hydroxide is (4.8-5.2):
1.
3. The preparation method according to claim 1 or 2, characterized in that: The chromium trioxide is mixed with sodium hydroxide in a solid form.
4. The preparation method according to claim 1, characterized in that: The drying temperature is 80-120°C; and / or, The drying time is 8-12 hours.
5. The preparation method according to claim 1, characterized in that: The reaction was carried out under an oxygen atmosphere.
6. The preparation method according to claim 5, characterized in that: The oxygen volume content in the oxygen atmosphere is 90-100%.
7. The preparation method according to claim 6, characterized in that: The heating rate of the reaction is 1-5°C / min; and / or, The reaction time is 40-50h.
8. The preparation method according to claim 1, characterized in that: The mixing includes: first mixing at 1000-1200 r / min for 10-12 min, and then mixing at 2500-3000 r / min for 15-20 min.
9. The sodium ion positive electrode material obtained by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a sodium ion positive electrode material prepared by the preparation method according to any one of claims 1 to 8; Preferably, the sodium ion battery further comprises a negative electrode plate, and the negative electrode active material of the negative electrode plate comprises graphite.